1993
DOI: 10.1016/0735-1097(93)90060-e
|View full text |Cite
|
Sign up to set email alerts
|

Planimetry of orifice area in aortic stenosis using multiplane transesophageal ecocardiography

Abstract: Multiplane transesophageal echocardiography is a practical and accurate clinical tool for the assessment of the severity of aortic stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(46 citation statements)
references
References 17 publications
1
42
0
3
Order By: Relevance
“…These data are in accordance with reports on multiplane TEE which showed that structures with a complex spatial orientation such as aortic valve, ascending aorta, aortic arch, and coronary arteries are more easily and completely assessed with multiplane TEE [7,[13][14][15][16][17][18] . Thus, multiplane TEE appears to be an ideal method to give detailed anatomical information about the morphology of a dissection, and can also show the consequences and complications of proximal extension.…”
Section: Discussionsupporting
confidence: 81%
“…These data are in accordance with reports on multiplane TEE which showed that structures with a complex spatial orientation such as aortic valve, ascending aorta, aortic arch, and coronary arteries are more easily and completely assessed with multiplane TEE [7,[13][14][15][16][17][18] . Thus, multiplane TEE appears to be an ideal method to give detailed anatomical information about the morphology of a dissection, and can also show the consequences and complications of proximal extension.…”
Section: Discussionsupporting
confidence: 81%
“…Other diagnostic tools should be considered to assess morphology and hemodynamics of the stenotic valve. This may include transesophageal echocardiography, 31 magnetic resonance imaging, 32 and, rarely, cardiac catheterization, 33 as outlined in the American Heart Association/ American College of Cardiology and European Society of Cardiology guidelines. 10 -12 Several additional echocardiographic parameters have been proposed for a better definition of the severity of aortic stenosis and imminent risk (energy loss index, 34,35 stroke work loss, 36,37 resistance, 38 and valvuloarterial impedance 39,40 ), but their utility and prognostic impact still must be proven in larger-scale, prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…A Cc below 1 in mitral stenosis implies that effective valve area is less than anatomic valve area; however, in aortic stenosis Cc was established empirically as 1, indicating that AVAe is equal to AVAa. Several studies of the correlation between AVAe estimated by Doppler echocardiography and valve area estimated by cardiac catheterization, TEE, computed tomography and magnetic resonance demonstrated that AVAa is greater than AVAe, because AVAe is calculated using the maximal velocity at the vena contracta, a hydrodynamic area located above AVAa [12] [18]- [23]. Clavel et al [24] studied with computed tomography and echocardiography patients with aortic stenosis and found a modest correlation [32] [33].…”
Section: Discussionmentioning
confidence: 99%
“…A multiplane Toshiba 5 MHz transducer was used and planimetry of the aortic valve was obtained from the short-axis view [12]. The view was considered adequate for planimetry if the aorta had a circular shape and all cusps were visualized simultaneously.…”
Section: Transesophageal Echocardiographymentioning
confidence: 99%